Energy-carbon-water footprint of sugarcane bioenergy: A district-level life cycle assessment in the state of Maharashtra, India. (November 2021) - Hiloidhari, Moonmoon; Vijay, Vandit; Banerjee, Rangan; Baruah, D.C.; Rao, Anand B.
Abstract: Sugarcane bagasse-based cogeneration contributes significantly to bioenergy conversion in India and therefore, appropriate performance analysis is required considering the regional factors. Further increase of sugarcane bioenergy is expected in India with the Government's mandate to enhance the share of renewable energy by 2030. Herein this study, district-wise sugarcane bagasse cogeneration potential is assessed in the state Maharashtra, India. Variations in energy, carbon and water footprint of energy generated from bagasse-based cogeneration plants are also assessed for all the districts considering farm to gate attributional life cycle assessment (ALCA). Avoided product function (also called as System expansion) of simaPro 9.2 LCA software is used to assess the environmental benefits of sugarcane waste or by-products (leaves and tops, press-mud and bagasse ash). The annual bagasse production potential in Maharashtra is 19 million tonne, equivalent to 8206 GWh of cogenerated electricity. The potential varies markedly among the districts (2–1500 GWh). Nearly 81 % of cogeneration potential is concentrated in 6 districts alone. The life cycle carbon footprint (0.075–0.2 kg CO2 e/kWh), the energy footprint (0.75–2.12 MJ/kWh) and the water footprint (206–516 L/kWh)-all the three estimated on the life cycle basis- differ considerably among the districts. The nexus among water, energy, and carbon footprint for sugarcane bioenergy is also analyzed to understand the complex interconnectivities among these individual resources. Cultivating high yielding varieties, use of renewable energy-based micro-irrigation, and installing modern cogeneration technology can lower the estimated carbon, energy and water footprint by up to 50 %. Such measures will help enhance farmers' income while addressing the sustainability issues in India. Highlights: District-wise resource analysis and bagasse cogeneration LCA in Maharashtra, India. Bagasse Cogeneration potential varies from 2 to 1500 GWh among the districts. Energy Return on Investment of cogeneration electricity ranges from 1.7 to 4.8. Cogeneration footprints: Carbon (0.075–0.2 kg CO2 e/kWh), Water (206–516 L/kWh). Energy-Carbon-Water nexus management and economic opportunities for farmers suggested.